Integrated management decision-making: A futuristic model for police organizations - Taylor, Robert W. (American journal of criminal justice, 1984)
This study examines the theoretical issues concerning decision-making and advances a new and innovative model emphasizing the integration of the organization and environment. Political, economic, social, cultural, and other community factors are highlighted as major influences affecting the police arena. Finally, the model is discussed as a catalyst for change in current police management thinking. Futuristic concepts of organization-environmental learning, long-range planning, and strategic modeling are suggested as necessary improvements in police decision-making.